Bibliometric and visualization analysis of matrix metalloproteinases in ischemic stroke from 1992 to 2022 - YiKun Gao; Yina Li; Shi Feng; Lijuan Gu (Frontiers in Neuroscience, 2023)
BackgroundMatrix metalloproteinases (MMPs) are important players in the complex pathophysiology of ischemic stroke (IS). Recent studies have shown that tremendous progress has been made in the research of MMPs in IS. However, a comprehensive bibliometric analysis is lacking in this research field. This study aimed to introduce the research status as well as hotspots and explore the field of MMPs in IS from a bibliometric perspective.MethodsThis study collected 1,441 records related to MMPs in IS from 1979 to 2022 in the web of science core collection (WoSCC) database, among them the first paper was published in 1992. CiteSpace, VOSviewer, and R package “bibliometrix” software were used to analyze the publication type, author, institution, country, keywords, and other relevant data in detail, and made descriptive statistics to provide new ideas for future clinical and scientific research.ResultsThe change in the number of publications related to MMPs in IS can be divided into three stages: the first stage was from 1992 to 2012, when the number of publications increased steadily; the second stage was from 2013 to 2017, when the number of publications was relatively stable; the third stage was from 2018 to 2022, when the number of publications began to decline. The United States and China, contributing more than 64% of publications, were the main drivers for research in this field. Universities in the United States were the most active institutions and contributed the most publications. STROKE is the most popular journal in this field with the largest publications as well as the most co-cited journal. Rosenberg GA was the most prolific writer and has the most citations. “Clinical,” “Medical,” “Neurology,” “Immunology” and “Biochemistry molecular biology” were the main research areas of MMPs in IS. “Molecular regulation,” “Metalloproteinase-9 concentration,” “Clinical translation” and “Cerebral ischemia–reperfusion” are the primary keywords clusters in this field.ConclusionThis is the first bibliometric study that comprehensively mapped out the knowledge structure and development trends in the research field of MMPs in IS in recent 30 years, which will provide a reference for scholars studying this field.